O conceito de território: uma análise dos documentos nacionais de geografia para o ensino médio - Alencar Junior, Clodoaldo Gomes (2009)
This study aims at investigating the concept of territory in the national documents of Geography for High School grade levels, PCNEM, from 1999, PCN+, from 2002 and OCEM, from 2006. It starts with a brief contextualization of political, economic and social changes in the 90´s that have influenced the education, mainly in the High School. We analyzed and tried to read the national documents of Geography from a critical point of view looking for particular characteristics of the concept of territory stated in these documents. We tried to know, therefore, the similarities and differences that permeate this concept, so we identified the theoretical lines and the common and singular components in each document, as also the discussion about the concept of territory, which is expanded beyond the idea of State-Nation. The investigation showed the effect on High School brought about by the changes in the productive process, either by the acquisition of basic competences for job opportunities, or by an education throughout a life, not to mention the ideas of competence that permeate the three national documents for High school grade levels which have been analyzed. The research allows the understanding of how the PCNEM and the OCEM enlarge the approach of the concept of territory to other scales, besides the scale of State-Nation while the PCN+ approaches in their board of topics only one scale of State-Nation